The global, regional, and national impact of laryngeal cancer from 1990 to 2021, along with forecasts for 2050: a comprehensive analysis for the Global Burden of Disease 2021 research - Duan, Tingting; Zou, Yuxia; Liu, Xuan; Du, Yue; Li, Ruihu; Cai, Jingxiang; Li, Jumei; Wang, Xiaofeng; Zhou, Xuejun; Ding, Shun (Frontiers in Oncology, 2025)
BackgroundLaryngeal cancer (LC), the second most common head and neck malignancy, with significant global geographical disparities in incidence and mortality, was analyzed using 2021 Global Burden of Disease (GBD) data to assess Socio-Demographic Index (SDI) correlations and project disease burden through 2050, aiming to reduce its global impact.MethodsUsing data from the GBD 2021, we investigated the incidence, prevalence, deaths, and Disability-Adjusted Life Years (DALYs) of LC, as well as trends, age-sex-time patterns, driving factors, and projections up to 2050.ResultsIn 2021, LC increased with age and decreased after the age of 70. The incidence and mortality rates of male patients are much higher than those of female patients, and the gap between men and women gradually narrows after the age of 70. From 1990 to 2021, the overall disease burden of LC globally showed a downward trend and is expected to further decline by 2050. However, there are significant differences among different countries and regions. In high SDI regions, the disease burden gradually decreases after reaching its peak, while in low SDI regions, the reduction or increase in the disease burden is relatively small. Population growth and aging are the main factors leading to the increase in the LC burden, but epidemiological changes have alleviated this burden to a certain extent. Smoking and excessive alcohol consumption are the main risk factors for LC.ConclusionsWhile the global LC burden has moderated, significant disparities persist across SDI regions. Healthcare quality improvements and targeted prevention, with this analysis offering evidence-based guidance for public health strategy formulation.